Penggunaan Media e-Learning Berbasis Edmodo Dalam Pembelajaran English for Business - Dharmawati . (Query: Journal of Information Systems, 2017)
The use of edmodo in learning English for Business was aimed to described the use of edmodo in teaching learning English for Business. The subject of this research was the second semester of Information System students in STT Harapan Medan. This research was research and development and the method was qualitative research and the data used was observation among English lecturer and students. The result of this research was classroom interaction among English lecture and students in edmodo application, teaching learning English for Business become interesting and students were active to use their English because the lecturer push them to use English in writing comments, message and also when they had presentation infront of the class. However, there were some students’ mistakes when they wrote comments, and also when they had English presentation.